Ragam Metode penetapan hukum Islam kontemporer - Firdaus Firdaus; Ahmad Juneidi; Lola Astari; Firda Mustika Sari (Universitas Cokroaminoto Yogyakarta, 2020)
The first source of Islamic law is al-Qur'an, after the new Al-Qur'an, the Hadith of the Prophet SAW. When searching for a law that not contained in the Al-Qur’an and al-Hadith, way to do is using ijtihad (raʻyu). This ijtihad is the mobilization of all the abilities of a fuqaha 'to find sharia law,' and the person who discovered it was named Mujtahid. The scholars in using this ra'yu issued many methods as a tool to install the law, such as: ijma 'which is the ahlul ilmi agreement on the law of an event with the condition that the scientists gather at the same time Qiyas, istihsan, istishab, 'urf. The purpose of this paper is to explain contemporary ijtihad methods that can be used to perform istinbath law. The discussion discussed in this paper is about the various ways of establishing modern Islamic law. The methodology used in this paper is the type of library (library research), namely by referring to books relating to fiqh and ushul fiqh. From the author's analysis that the methods used to establish Islamic law in the contemporary period are no different from the methods used previously, namely sourced from the Qur'an, Hadith, and ijtihad of the scholars who have mujtahid criteria.